Are the Romanian natural protected areas properly covering the wetland? - PETRIŞOR Alexandru-Ionuţ; PETRIŞOR Liliana Elza (Scientific Annals of the Danube Delta Institute, 2020)
Wetlands host an important biodiversity, provide important ecosystem services, and are threatened and vulnerable ecosystems, representing a priority for the conservation of biodiversity. Previous studies have attempted to assess the efficiency of conservation in Romania through the natural protected areas. The current study attempts to provide an overall picture, using free available geospatial data on natural protected areas and land cover. The methodology consisted of computations performed using the GIS. The results indicate a very good conservation of wetlands (90% of their area). However, if the Danube Delta Biosphere Reserve is excluded, the percentage drops down to 62%. Wetlands make up an important share of biosphere reserves, world heritage sites, and Ramsar sites. Overall, 11% of the land cover of natural protected areas consists of wetlands. The results indicate that the natural protected areas system accounts for wetlands in particular, but improvements are still possible.